Design and analysis of 2 in 1 sand sieving machine - Zulkharnain, Adam Mikhail (2025)
The sand sieving machine successfully improves the process of separating sand mixtures by ensuring the user safety and efficiency. Its innovative design ensures the sand is filtered without risk to the operator, while it’s rotating the mixture of sand. This machine also provides optimal power and speed for effective filtration with minimal physical effort. The project has achieved a lot of achievements, including enhanced sustainability, efficiency, and safety. By promoting eco-friendly practices, the machine addresses issues related to energy waste, time consumption, and environmental impact. Thus, it will offer a progressive solution to these challenges